Detecting Behavioural Additionality: An Empirical Study on the Impact of Public R&D Funding on Firms' Cooperative Behaviour in Germany - Andreas Fier; Birgit Aschhoff; Heide Löhlein (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
Subsidising research networks has become a popular instrument in technology policies, driven mainly by expected positive spillovers. In particular, the stimulation of R&D co-operation between scientific institutions and industry is considered as most promising. In the context of policy evaluation we analyse if public R&D funding is suitable for influencing firms' collaborative behaviour in the intended way and where applicable, if a lasting change results. The empirical analysis is based on German CIS data and a supplemental telephone survey. Using a nearest-neighbour matching approach we find that R&D funding is indeed a particularly valuable tool for the linking of science into industry R&D partnerships. However, we also show in a bivariate probit analysis that newly initiated R&D co-operations with science are less likely to be continued after funding has ended compared to already existing co-operations. Therefore, the behavioural change induced by public funding is not necessarily longlived.
More recent version: http://hdl.handle.net/10419/24704
Keywords: O32; O38; H32; L22; C20; 330; Public Funding; Firm Behaviour; Policy Evaluation; R&D Co-operation; Forschungssubvention; Forschungskooperation; Business Network; Wirtschaftspolitische Wirkungsanalyse; Schätzung; Deutschland